Repercussões da pandemia da Covid-19 no desenvolvimento de lactentes de 18 a 24 meses - Hermes, Letícia (2023)
Introduction: Infant development permeates interrelated domains (cognition, language, motor and socio-behavioral) and is related, in addition to biological issues, to a series of factors linked to the environment in which the infant lives. From this premise, it is questioned how much the health restrictions of the Covid-19 Pandemic may have had an impact on the development of infants. Objective: To investigate the repercussions of the Covid-19 Pandemic on motor and linguistic outcomes of neurotypical infantren aged 18 to 24 months. Methodology: Infants aged 18 to 24 months, born at term, neurotypical, without diagnosis of malformations or syndromes, were included in this study. The data collection was performed through anamnesis interview and self-completed questionnaires; Hearing Assessment; in addition to this, cognitive screening and complete batteries of motor and language scales from the Bayley Scales of Infant and Toddler Development®, Third Edition (Bayley III), were used. Results: A total of 44 infants participated in the study (22 in the Study Group - SG, evaluated in the /AFETR THE post-pandemic period; and 22 in the Control Group - CG, evaluated in BEFORE the pre-pandemic period). Regarding comparisons between groups, the SG presented a tendency towards an advantage over the CG in language-related outcomes and the CG had a better performance in terms of gross motor skills, possibly associated with the restrictions imposed by the Pandemic. Maternal schooling and family income differed between groups, favoring the SG, which may have been compensated for the restrictive effects of social distancing measures. When analyzed in the SG only, the associations between aspects of the routine altered by the Pandemic, the language outcomes were especially associated with the mother's work regime, paternal education, living with both parents and the interest in seeking the evaluation, the latter, as a marker of parental interest in the development of their infantren. The time used in television and s also pending time with other infantren, interfered in this domain. Regarding about the motor domain, the fine motor was associated with family income and the gross motor with gestational stress during the Pandemic. Conclusion: The Covid-19 Pandemic structurally modified routines and social relationships, however, some social and environmental factors may have protected the sample that experienced the outbreak (SG), such as maternal education and family income. As some routines can be perpetuated, even with a return to normality, new studies with a longitudinal design and more robust samples are suggested in order to elucidate and measure the real impact of the Pandemic on this generation.